State Building Challenges and the European Integration Process: The Kosovo Case - Zenun HALILI (Eastern European Journal of Regional Studies, 2018)
Kosovo, a new state which is in the process of international recognition of its statehood, after the 1999 war, and until the declaration of independence in 2008, has faced a number of challenges during its efforts to build the democratic system and order. Following the declaration of independence and a considerable number of international recognitions, Kosovo’s new democratic institutions are taking their responsibilities for the country's integration into the European Union. This paper provides one overview of state building challenges and the European integration process of the Republic of Kosovo. Kosovo has its old and new history, which was decided by the great powers in London, Berlin, Paris, in Yalta and Potsdam, and later in Dayton and Rambouillet. The purpose of this paper is to examine the historical roots of the independence movement among Kosovo Albanians, until the declaration of independence on February 17, 2008, and the state-creating challenges of the Kosovo state. Like other Western Balkan aspiring members, Kosovo's politicians and its population are fully committed to the process of European Integration. Being the last state from the Balkan Peninsula, Kosovo signed with EU a Stabilization and Association Agreement. EU membership is on the horizon, but Kosovo expects great work to achieve its objective.